2010
DOI: 10.1002/pip.1008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of defect type on hydrogen passivation efficacy in multicrystalline silicon solar cells

Abstract: We examine the effectiveness of hydrogen passivation as a function of defect type and microstructure at grain boundaries (GBs) in multicrystalline silicon. We analyze a solar cell with alternating mm‐wide bare and SiNx‐coated stripes using laser‐beam‐induced current, electron backscatter diffraction, X‐ray fluorescence microscopy, and defect etching to correlate pre‐ and post‐hydrogenation recombination activity with GB character, density of iron‐silicide nanoprecipitates, and dislocations. A strong correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…On the contrary, no link between the twin boundary density and the electrical activity was observed. These observations are consistent with and , where it was shown that it is the presence of dislocations along the twin boundaries that limits the ability of hydrogen to passivate them. This depends on the coincidence site lattice of the twin boundaries, the Σ3 being the less favourable to dislocation occurrence.…”
Section: Status Of the Rst Technologysupporting
confidence: 88%
“…On the contrary, no link between the twin boundary density and the electrical activity was observed. These observations are consistent with and , where it was shown that it is the presence of dislocations along the twin boundaries that limits the ability of hydrogen to passivate them. This depends on the coincidence site lattice of the twin boundaries, the Σ3 being the less favourable to dislocation occurrence.…”
Section: Status Of the Rst Technologysupporting
confidence: 88%
“…In good agreement with the l-XRF of Buonassisi et al, 44 they found that higher order CSL GB character and higher metal contamination lead to higher EBIC contrast. Bertoni et al 61 found higher GB recombination activity after hydrogenation strongly depended on the dislocation density and/or faceting along the GB.…”
Section: Appendix B: Assessment Of Assumptions For Comparisons Of Expmentioning
confidence: 99%
“…Preparation procedures have been reported elsewhere [8]. The electrical performance was characterized using laser beam-induced current (SR-LBIC) [9] at the University of Konstanz at 833 nm and 910 nm.…”
Section: Resultsmentioning
confidence: 99%